1994
DOI: 10.1128/iai.62.6.2633-2638.1994
|View full text |Cite
|
Sign up to set email alerts
|

F17-like fimbriae from an invasive Escherichia coli strain producing cytotoxic necrotizing factor type 2 toxin

Abstract: The F17b fimbriae encoded by the transmissible virulence plasmid Vir, also coding for cytotoxic necrotizing factor type 2, were characterized. A 5.7-kb region of Vir mediates in vitro N-acetylglucosamine-sensitive adhesion to calf intestinal villi. Sequence analysis revealed that this region codes for a structural subunit and an adhesin closely related to the F17-A and F17-G proteins encoded by the F17 fimbrial gene cluster. The F17b-A gene presents an open reading frame of 540 bp encoding a polypeptide of 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 26 publications
2
31
0
1
Order By: Relevance
“…This region is a pathogenicity island (PAI) inserted near the pheR tRNA gene (Swenson et al, 1996). Conversely, most of the CNF2-producing strains are not haemolytic and produce a F17 fimbrial adhesin which mediates adhesion to calf villi (El Mazouari et al, 1994;Oswald et al, 1991). Certain CNF2-producing strains may also produce an AFA-like adhesin (Mainil et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This region is a pathogenicity island (PAI) inserted near the pheR tRNA gene (Swenson et al, 1996). Conversely, most of the CNF2-producing strains are not haemolytic and produce a F17 fimbrial adhesin which mediates adhesion to calf villi (El Mazouari et al, 1994;Oswald et al, 1991). Certain CNF2-producing strains may also produce an AFA-like adhesin (Mainil et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Certain CNF2-producing strains may also produce an AFA-like adhesin (Mainil et al, 1997). All these factors, CNF2 and adhesins, are encoded by the Vir plasmid (El Mazouari et al, 1994;Mainil et al, 1997;Oswald et al, 1989). This plasmid is a large F-like conjugative plasmid of 140 kb which was first described in E. coli strains isolated from septicaemic calves (Lopez-Alvarez et al, 1980;Smith, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CS31A was prominent among CNF1-producing strains but was not detected among bovine E. coli strains producing the closely related CNF2 toxin [10]. In contrast, previous studies have demonstrated that CNF2 toxin is often associated with F17 ¢mbriae [3,10].…”
Section: Genetic Detection Of Adhesins and Toxin Genesmentioning
confidence: 71%
“…The cytotoxic necrotizing factor type I (CNF1) is a chromosome-encoded toxin produced by E. coli strains isolated from diarrhea, septicemia or UTI in humans, piglets or calves [2]. The cytotoxic necrotizing factor type II (CNF2) expressed by E. coli strains isolated from calves and lambs with enteritis or bacteremia is highly homologous to CNF1 [3]. More recently, a low-molecularmass peptide named enteroaggregative E. coli heatstable enterotoxin I (EAST 1) produced by enteroag-gregative E. coli (EAggEC) has been described [4].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas CNF1 is encoded by the chromosome (Falbo et al, 1993), CNF2 is determined by a Vir plasmid . At least two other virulence markers are encoded by Vir plasmids along with CNF2: an F17-related ®mbria, which mediates the adherence of bacterial cells to calf intestinal villi (Oswald et al, 1991;El Mazouari et al, 1994) and a new type of ®mbrial adhesin, called AFA (Mainil et al, 1997). The role of CNF1 and CNF2 in the pathogenesis of E. coli infections is still uncertain but their necrotic and lethal properties in vivo and their ability to alter the cytoskeleton of cultured cells in vitro suggest that both cytotoxins may be true virulence factors Pohl et al, 1992).…”
Section: Introductionmentioning
confidence: 99%